ANALYTICAL READING - INTELLECTUAL FACTOR FOR THE FORMATION OF ANALYTICAL THINKING IN STUDENTS - Sh. A. Hasanov (Galaxy International Interdisciplinary Research Journal, 2021)
The article argues that analytical reading is an intellectual factor in the formation of analytical thinking in students.